IMPROVING LEARNING OUTCOMES IN EVEN SEMESTER CHRISTIAN RELIGIOUS EDUCATION AND CHARACTER EDUCATION SUBJECT MATTER HUMILITY WITH CHARACTER-BASED EXAMPLE METHODS FOR CLASS VII.10 STUDENTS OF SMP NEGERI 8 MEDAN T.P 2021/2022 - Marlys Pasaribu (Sean Institute, 2022)
Improving Learning Outcomes in Even Semester Christian Religious Education and Character Education Subject Matter Humility with Character-Based Example Methods for Class VII.10 Students of SMP Negeri 8 Medan TP 2021/2022 . Objective This research was carried out to improve student learning outcomes in class VII. 10 SMP Negeri 8 Medan for the 2021/2022 academic year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are students of class VII.10 SMP Negeri 8 Medan as many as 21 people, the instrument used to obtain data is by using tests, observing the range of values ​​for the test. are the highest and lowest values. Instrument which is used for data processing is to use the calculation of the total score of students who have not reached the KKM and the results of the scores that have reached the KKM. The KKM has been set, which is 75. There is an increase in the number of students who have completed Reaching the KKM (75), where in the initial test the number of students who have completed only 5 people (23%), increased to 11 people (50%) in the first cycle and then increased again to 17 students (80%) in cycle II. There was a decrease in the number of students who did not complete, where in the initial test the number of students who did not complete reached 16 people (76%), in the first cycle the students who did not complete decreased to 10 (50%) then in the second cycle it decreased again to 4 The students who did not complete ( 19 % ).